Decision Support System For Choosing The Best Class Guardian With Simple Additive Weighting Method: Decision Support System For Choosing The Best Class Guardian With Simple Additive Weighting Method - Dini Anggraini; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2019)
Education is one of the most important things that can bring progress in a country. This study aims to design and build a decision system for the selection of the best supervisor class that can help the selection of supervisor class using the Simple Additive Weighting (SAW) method with pedagogic, personality, social, professionalism, education assessments. The SAW method is a method that uses the weighted sum. With this method the optimal solution is sought from alternatives and certain criteria. In this study, the researcher conducted research at SMA 1 Perbaungan so that the selection of the best supervisor class was right on target.